Downregulation of lncRNA-11496 in the Brain Contributes to Microglia Apoptosis via Regulation of Mef2c in Chronic T. gondii Infection Mice - Sun, Xiahui; Wang, Ting; Wang, Yongliang; Ai, Kang; Pan, Ge; Li, Yan; Zhou, Chunxue; He, Shenyi; Cong, Hua (Frontiers in Molecular Neuroscience, 2020)
Though it is well known that chronic infections of Toxoplasma gondii are able to induce mental and behavioral disorders in host, little is known about the role of lncRNA (long noncoding RNA) in this pathological process. In this study, we employed an advanced lncRNAs and mRNAs integration chip (Affymetrix HTA 2.0) to detect the expression of both lncRNAs and mRNAs in T. gondii Chinese 1 strain infected mouse brain. As a result, for the first time, downregulation of lncRNA-11496 (NONMMUGO11496) was identified as the responsible factor for this pathological process. We showed that dysregulation of lncRNA-11496 affected proliferation, differentiation and apoptosis of mouse microglia. Furthermore, we proved that Mef2c (Myocyte-specific enhancer factor 2C), a member of the MEF2 subfamily, is the target gene of lncRNA-11496. In a more detailed study, we confirmed that lncRNA-11496 positively regulated the expression of Mef2c by binding to HDAC2 (histone deacetylase 2). Importantly, Mef2c itself could coordinate neuronal differentiation, survival, as well as synapse formation. Thus, our current study provides the first evidence in terms of the modulatory action of lncRNA in chronic T. gondii infected mouse brain, providing the solid scientific basis for using lncRNA-11496 as a therapeutic target to treat T. gondii induced neurological disorder.